Spondylodiscitis developing after epidural catheter use by direct contamination - Erol, FS; Kaplan, M; Kizirgil, A; Ozveren, MF (Saudi Med J, 2005)
Spondylodiscitis is a rare but serious complication of epidural catheter use. It is controversial as to which mechanism is responsible for development of this complication. It may develop due to direct contamination or hematogenous spreading. We report a 54-year-old woman who developed spondylodiscitis after epidural catheter was inserted and to whom analgesic and steroid treatment was given for chronic lumbar pain. In this case, each of 2 pathological mechanisms may be responsible. The diagnostic methods, mechanisms and management are discussed.